EFFECT OF DIFFERENT MEDIUM CHAIN FATTY ACIDS, CALCIUM BUTYRATE, AND SALINOMYCIN ON PERFORMANCE, NUTRIENT UTILIZATION, AND FERMENTATION PRODUCTS IN GASTROINTESTINAL TRACTS OF BROILER CHICKENS - M. Hejdysz; S. Kaczmarek; D. Józefiak; D. Jamroz; A. Rutkowski (Journal of Animal and Plant Sciences, 2018)
The objective of this study was to study efficacy of medium chain fatty acids (MCFAs), salinomycin, and butyric acid on growth performance, energy and nutrient availability, development of internal organs, and content of short chain fatty acids (SCFAs) in the gastrointestinal tract of broiler chickens. Nine hundred and sixty Ross 308 male broilers were used in this study. Birds were randomly assigned to 10 dietary treatments (12 replications each/8 birds in one replication). We used two types of diet [provocative (PD) and corn diet (MD)]; each diet was then split into five batches that were supplemented with either salinomycin (70.0 mg/kg); triglyceride form of capric and caprylic acid (3.0 g/kg; MCT 1.38:1); calcium butyrate (10.0 g/kg; CB); mixture of caproic, caprylic, and capric acids (8.3 g/kg; MCFA; 1:1:1); or without any supplement [control (C)]. The examined supplements exerted a positive effect on growth performance in MD-fed chickens only. Chickens fed with MCFA-supplemented MD diet were characterized with 10% gain in body weight and 5% lower feed conversion ratio (FCR) than that of birds in the control group. CB positively influenced the value of nitrogen corrected apparent metabolizable energy (AMEN) by about average 6% (PD and MD) in comparison to the control birds. Nitrogen retention was found to be changed only in PD. The highest positive change was found in birds of MCT group (25%) than that of birds in the control group. MCFA, MCT and CB  showed a favorable influence on the weight of gastrointestinal tract, in particular, the weight of the ileum, which was about 8% heavier than that of the control birds. The diet type and tested supplements significantly enhanced the content of SCFAs in broiler crop, ileum, and cecum digesta. In conclusion, the effect of tested supplements on the parameters determined depended on the type of diet, as confirmed by significant interactions. MCFA was found to be the best supplement in this study.
Keywords: Broilers; Salinomycin; Medium chain organic acids; Calcium butyrate